Polymerization potential of a bacterial CotA-laccase for β-naphthol: enzyme structure and comprehensive polymer characterization - Refaat, Marina; ElRakaiby, Marwa T.; El Hariri El Nokab, Mustapha; Es Sayed, Julien; Elshewy, Ahmed; Sebakhy, Khaled O.; Moneib, Nayera; Wang, Tuo; Smith, Thomas J.; Habib, Mohamed H. (Frontiers in Microbiology, 2024)
IntroductionLaccases are blue-multicopper containing enzymes that are known to play a role in the bioconversion of recalcitrant compounds. Their role in free radical polymerization of aromatic compounds for their valorization remains underexplored. In this study, we used a pBAD plasmid containing a previously characterized CotA laccase gene (abbreviated as Bli-Lacc) from Bacillus licheniformis strain ATCC 9945a to express this enzyme and explore its biotransformation/polymerization potential on β-naphthol.MethodsThe protein was expressed from TOP10 cells of Escherichia coli after successful transformation of the plasmid. Immobilized metal affinity chromatography (IMAC) was used to generate pure protein. The biocatalytic polymerization reaction was optimized based on temperature, pH and starting enzyme concentration. 1H and 13C solution nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), and solid-state NMR (ssNMR) were used to characterize the formed polymer. A one-gram conversion reaction was done to explore applicability of the reaction in a pilot-scale.ResultsThe polymerization reaction generated a brown precipitate, and its chemical structure was confirmed using 1H and 13C NMR and FTIR. SsNMR revealed the presence of two different orientational hydroxyl functional groups in the polymer in addition to the presence of a very small amount of ether linkages (< 2%). This analysis elucidated that polymerization occurred mainly on the carbons of the aromatic rings, rather than on the carbons attached to the hydroxyl groups, resulting in a condensed ring or polynuclear aromatic structure. The reaction was optimized, and the highest yield was attained under conditions of 37°C, pH 10 and a starting enzyme concentration of 440 nM in 50 mM phosphate buffer. A one-gram conversion yielded 216 mg of polymer as dry mass. The crystal structure of the enzyme was solved at 2.7 Å resolution using X-ray crystallography and presented with a hexagonal space group. The final structure was deposited in the Protein Databank (PDB) with an ID−9BD5.DiscussionThis article provides a green/enzymatic pathway for the remediation of phenolics and their valorization into potential useful polymeric materials. The comprehensive analysis of the formed polymer provides insight into its structure and functional moieties present. Based on the yield of the one-gram conversion, this synthetic method proves useful for a pilot-scale production level and opens opportunities to invest in using this polymer for industrial/environmental applications.